The Yemeni Civil War’s Impact On The Socio-Cultural Conditions Of The People In Yemen - Ahmad, Hilal; Hanafi, Imam (Universitas Islam Negeri Raden Intan Lampung, 2023)
This research is motivated by a civil war that began since the outbreak of the Arab Spring in Yemen in 2011 which until now has not shown perfect peace. This study has adopted descriptive qualitative research whose purpose of this study is to describe how the socio-cultural conditions of the Yemeni people are as a result of the protracted civil war. This research uses conflict theory proposed by Ralf Dahrendorf. The source of data in this study comes from books, journals and articles related to the object under study. Based on the research conducted, it can be concluded that the civil war that has occurred in Yemen since the Arab Spring in 2011 is due to differences in the interests of each group. In addition, the civil war in Yemen also has an impact on the socio-cultural conditions of Yemeni society. The impact caused during the civil conflict in Yemen greatly affects the socio-cultural conditions of the people in the Yemeni area, can be seen by the emergence of various kinds of changes that occur in society. Both in social, educational, cultural, and economic conditions. So it can be said that a conflict certainly creates a change and development. The conflict in Yemen has been going on for quite a long time and has occurred repeatedly because it has not reached a peace agreement, and also the conflict in Yemen has reached the stage of violence, namely war. So the changes that occur can be radical or structural changes to Yemeni society.